2012
DOI: 10.1038/ncb2608
|View full text |Cite
|
Sign up to set email alerts
|

β2-syntrophin and Par-3 promote an apicobasal Rac activity gradient at cell–cell junctions by differentially regulating Tiam1 activity

Abstract: Although Rac and its activator Tiam1 are known to stimulate cell-cell adhesion, the mechanisms regulating their activity in cell-cell junction formation are poorly understood. Here, we identify β2-syntrophin as a Tiam1 interactor required for optimal cell-cell adhesion. We show that during tight junction (TJ) assembly β2-syntrophin promotes Tiam1-Rac activity, in contrast to the function of the apical determinant Par-3 whose inhibition of Tiam1-Rac activity is necessary for TJ assembly. We further demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 67 publications
0
68
0
Order By: Relevance
“…At tight junctions, Par-3 inactivates Tiam1-Rac1 signalling, while -syntrophindependent Tiam1 localization activates Rac1 more basally, thereby generating a gradient of localized signalling, with different functions for tight junctions or adherens junctions [87]. Similar restricted zone of GTPase activation at zonula adherens is reported for RhoA, where positioning of ROCK1 by myosin II maintains RhoA activation by antagonizing the recruitment of Rnd3/p190RhoGAP, thereby preventing localized RhoA inactivation [88].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 78%
“…At tight junctions, Par-3 inactivates Tiam1-Rac1 signalling, while -syntrophindependent Tiam1 localization activates Rac1 more basally, thereby generating a gradient of localized signalling, with different functions for tight junctions or adherens junctions [87]. Similar restricted zone of GTPase activation at zonula adherens is reported for RhoA, where positioning of ROCK1 by myosin II maintains RhoA activation by antagonizing the recruitment of Rnd3/p190RhoGAP, thereby preventing localized RhoA inactivation [88].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 78%
“…Scale bars: 20 µm. β2-syntrophin was also shown to be crucial for junction assembly and apical-basal polarity in epithelial cells (Mack et al, 2012), thus syntrophins, as alternative scaffolds, might support Scribble in the junctional recruitment of DLC3. Biochemical experiments showed that the DLC3-Scribble interaction is mediated mainly by the Scribble PDZ3 domain, which also interacts with the planar cell polarity protein Vangl (Courbard et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Rac activation, for example, is controlled by the GEF protein Tiam, which itself is activated by the basolateral scaffold β2-Syntrophin and inhibited by apical Par3 (Mack et al, 2012;Mertens et al, 2005;Nishimura et al, 2005). Scribble contributes to spatially controlled Rho activation by targeting β-Pix (also known as ARHGEF7), a GEF for Rac and Cdc42 to adherens junctions to form a signaling complex with PAK2 regulating normal epithelial morphogenesis (Frank et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RhoA is active at contacts between NC cells (CarmonaFontaine et al, 2008) and ROCK phosphorylation of Par3 has been shown to disrupt formation of the Par3-aPKC-Par6 complex, through which Par3 often acts (Nakayama et al, 2008). However, ROCK phosphorylation of Par3 does not affect Par3-Tiam2 interactions (Nakayama et al, 2008), suggesting that Par3 is likely to regulate RacGEFs independently of its involvement in the Par complex, as has been shown for the regulation of Rac by Par3 in embryonic kidney cells (Mack et al, 2012).…”
Section: Research Articlementioning
confidence: 97%
“…Par3 promotes the maturation of the cell adhesion complex and has been linked to the regulation of microtubule dynamics and Rac1 activity through interaction with the Rac-GEF Tiam1 (Chen et al, 2013;Chen and Macara, 2005;Mack et al, 2012;Mertens et al, 2005;Mishima et al, 2002;Xue et al, 2013). In epithelial cells, Par3 associates with cell-cell adhesion complexes and appears to be important for establishing apicobasal polarity; however, whether Par3 controls PCP during CIL remains to be investigated.…”
mentioning
confidence: 99%